PENGEMBANGAN CERITA PENDEK ANAK TERINTEGRASI BUDAYA SEKOLAH UNTUK MEMBACA PEMAHAMAN KRITIS KELAS IV SD ISLAM AL AZHAR 13 RAWAMANGUN - Mita Meriska; Juhana Sakmal; Ika Lestari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to develop a school-culture integrated children's short story as a supplementary reading material to support critical reading comprehension among fourth-grade elementary school students. The study employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The participants included three expert validators (material, language, and media experts) and fourth-grade students of SD Islam Al Azhar 13 Rawamangun. Data were collected through interviews, expert validation sheets, student response questionnaires, and critical reading comprehension tests. The results showed that the developed product entitled “Manisnya Kok Beda?” achieved a feasibility score of 89.06% from material experts, 85.42% from language experts, and 91.67% from media experts, all categorized as highly feasible. Student responses in one-to-one, small-group, and field trials reached 97.50%, 97.92%, and 94.71%, respectively, indicating highly positive acceptance. The average critical reading comprehension score increased from 73.56 in the pretest to 86.95 in the posttest, with an N-Gain score of 0.51, categorized as moderate. The findings indicate that integrating school culture into children's literature provides contextual learning experiences that support the development of critical reading comprehension skills. Therefore, the developed short story is considered feasible and useful as supplementary reading material for elementary school students.